Implementation of Ad-Dararu Yuzalu Principle in the MUI Fatwa on the Law of Global Climate Change Control - Khairatun Hisan; Asmuni Asmuni (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2026)
Climate change has become a global crisis that threatens various sectors of life and the sustainability of ecosystems. In response to this phenomenon, the Indonesian Ulema Council (MUI) issued Fatwa Number 86 of 2023 concerning the Law on Global Climate Change Control. This study aims to analyze the implementation of the fiqh principle of ad-dararu yuzalu (harm must be eliminated) in the substance of the fatwa. The research method used is normative legal research with an usul al-fiqh approach. The primary data source is the text of MUI Fatwa No. 86 of 2023, while secondary data includes usul al-fiqh literature, fiqh rules, and scientific articles related to the environment. Data collection techniques were carried out through literature study and analyzed qualitatively and normatively. The results of the study show that the ad-dararu yuzalu rule is the main theological-juridical basis for identifying the impact of climate change as a form of dharar (harm) that threatens the five basic aspects of maqashid sharia (religion, life, intellect, lineage, and property) as well as environmental sustainability. The implementation of those manifest principles in the prohibition of all actions that damage nature and trigger climate crises, as well as the obligation for governments, businesses, and communities to undertake concrete mitigation and adaptation efforts to maintain ecosystem balance for future generations.